Application of Excavation Management Theoretical Measures in Tunneling Works for MRT3 Projec - Nor Shahhira Binti Mohd Shomee; Muhamad Faiz Bin Abd Latif; Muhammad Shazwan Bin Salimin (Progress in Engineering Application and Technology, 2022)
Apart from maintaining the efficiency of the excavation process, the Excavation Management System should be considered to avoid over-excavation, which can lead to sinkholes or ground settling during the excavation process. There are several ways for calculating the amount of excavated material based on the measurements. These can be expressed as excavated volume, mass, or dry mass using various formulae. Measurement errors, mechanical, electrical, and hydraulic concerns, the influence of time, and changing geology are all examples of such influences. The findings in this research indicate that the use of theoretical methods in calculating outflow rates which are related resulting in over-excavation laid on the behaviour of the different calculation methods, during situations such as a face collapse, calibration error of sensors, water inflows or compressed air interventions. If we are successful, our country’s excavation tunnelling EMS will develop in accordance with that of other industrialised countries. It also provides engineers with tools for detecting early indicators of over-excavation.